Konsep Penyusunan Perencanaan Evaluasi Hasil Belajar - Diah Robiatul Adawiah; Puji Ambarwati; Pupu Marpuah; Encep Syarifudin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The first step that needs to be done in evaluation activities is to make a plan. This planning is important because it will affect the next steps, and even affect the effectiveness of the overall evaluation procedure. This study aims to discuss the planning that must be prepared in the evaluation of learning outcomes. The method used in this study is a library research approach, this data collection uses a method of searching from various sources such as journals and research that has been studied. The results of the study show that the steps that need to be taken in planning an evaluation of learning outcomes include (1) Formulating the objectives of the evaluation (2) Determining the aspects to be evaluated (3) Selecting and determining the techniques to be used in the evaluation (4) Preparing the evaluation tools to be used in the evaluation (5) Determining the evaluation benchmarks (6) Determining the frequency of evaluation activities (7) Presenting the test (8) Processing the test results (9) Reporting evaluation results, and (10) Use of evaluation results. Through this careful evaluation planning, it is possible to set behavioral objectives or indicators to be achieved, to prepare for the collection of data and information needed and to be able to use the right time.